CONTEMPORARY MIGRATION CRISIS IN EUROPE AND ITS IMPACT ON SOCIO-POLITICAL SITUATION IN GERMANY - Garczewski, Krzysztof (Torun International Studies, 2017)
Migration crisis is currently one of the biggest challenges facing EU states. Te role of this issue in the German socio-political discourse in 2015–2016 is the main focus of the analysis presented in this paper. Among all members of the EU, Germany accepted majority of the migrants as a result of opening the borders in the late summer 2015.